2021
DOI: 10.3390/chemistry3010015
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Conformation of 3,2′:6′,3″-Terpyridine in [Cu2(μ-OAc)4(3,2′:6′,3″-tpy)]n 1D-Polymers

Abstract: We report the preparation and characterization of 4′-([1,1′-biphenyl]-4-yl)-3,2′:6′,3″-terpyridine (1), 4′-(4′-fluoro-[1,1′-biphenyl]-4-yl)-3,2′:6′,3″-terpyridine (2), 4′-(4′-chloro-[1,1′-biphenyl]-4-yl)-3,2′:6′,3″-terpyridine (3), 4′-(4′-bromo-[1,1′-biphenyl]-4-yl)-3,2′:6′,3″-terpyridine (4), and 4′-(4′-methyl-[1,1′-biphenyl]-4-yl)-3,2′:6′,3″-terpyridine (5), and their reactions with copper(II) acetate. Single-crystal structures of the [Cu2(μ-OAc)4L]n 1D-coordination polymers with L = 1–5 have been determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
(78 reference statements)
0
18
0
Order By: Relevance
“…Replacing the carboxylic acid functionality in ligand H4 by a sulfonic acid to give H13 (Figure 6) has an interesting effect on the assembly. The reaction between Na [13] and CdCl2 under hydrothermal conditions produced [Cd( 13)Cl]n which possesses a 1D-ladder structure. The compound was prepared as a model system with which to compare the photophysical behaviors of lanthanoid(III) metal analogs, and the structure is described only in the supporting information in the original work [43].…”
Section: Assemblies Containing Zn(ii) and 22':6'2"-tpy Ligands Functionalized With Carboxylate Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing the carboxylic acid functionality in ligand H4 by a sulfonic acid to give H13 (Figure 6) has an interesting effect on the assembly. The reaction between Na [13] and CdCl2 under hydrothermal conditions produced [Cd( 13)Cl]n which possesses a 1D-ladder structure. The compound was prepared as a model system with which to compare the photophysical behaviors of lanthanoid(III) metal analogs, and the structure is described only in the supporting information in the original work [43].…”
Section: Assemblies Containing Zn(ii) and 22':6'2"-tpy Ligands Functionalized With Carboxylate Donorsmentioning
confidence: 99%
“…Some isomers of tpy are conformationally flexible, and this is illustrated in Scheme 4 for 3,2':6',3"-tpy for which three planar limiting conformations exist. The ligand conformation can be switched in the solid-state structure by introducing different substituents [10], and this impacts the structures of coordination polymers containing such ligands [11][12][13]. Note that while conformations A and B in Scheme 4 are divergent, conformation C is convergent and often leads to discrete molecular complexes, for example, the dizinc(II) macrocycle [14] shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these ligands only coordinate to metal ions through the outer pyridine rings. While 4,2':6',4"-tpy presents a V-shaped linker between metal centres (Scheme 1), 3,2':6',3"-tpy is conformationally flexible by virtue of inter-ring C-C bond rotation [7,[9][10][11][12]. The three limiting planar conformations of 3,2':6',3"-tpy are shown in Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation was extended to isomeric C4-alkyloxy substituents, and revealed significant structural perturbation on going from n-butyl to branched isomers, but only subtle changes across the series rac-4-butan-2-yl, 2-methylpropyl and tert-butyl peripheral groups [21]. We have also investigated the effects of introducing different halogen-substituents in 3,2':6',3"-tpy and 4,2':6',4"-tpy ligands containing 4'-biphenyl-4-yl substituents [12,22]. The most recent of these studies focused on ligands 1-5 (Scheme 3) and revealed that the 1D-coordination polymers [Cu2(μ-OAc)4 (2)]n and [Cu2(μ-OAc)4 (3)]n are isostructural featuring inter-chain H...H and H...F interactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation